Tailoring Nanoparticle-Biofilm Interactions to Increase the Efficacy of Antimicrobial Agents Against Staphylococcus aureus - Fulaz S (Dove Medical Press, 2020)
Stephanie Fulaz,1,* Henry Devlin,1,* Stefania Vitale,1 Laura Quinn,1 James P O’Gara,2 Eoin Casey1 1UCD School of Chemical and Bioprocess Engineering, University College Dublin, Dublin, Ireland; 2Department of Microbiology, School of Natural Sciences, National University of Ireland, Galway, Ireland*These authors contributed equally to this workCorrespondence: Eoin CaseyUCD School of Chemical and Bioprocess Engineering, University College Dublin, Belfield, Dublin 4, Dublin, IrelandEmail eoin.casey@ucd.ieBackground: Considering the timeline required for the development of novel antimicrobial drugs, increased attention should be given to repurposing old drugs and improving antimicrobial efficacy, particularly for chronic infections associated with biofilms. Methicillin-susceptible Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus (MRSA) are common causes of biofilm-associated infections but produce different biofilm matrices. MSSA biofilm cells are typically embedded in an extracellular polysaccharide matrix, whereas MRSA biofilms comprise predominantly of surface proteins and extracellular DNA (eDNA). Nanoparticles (NPs) have the potential to enhance the delivery of antimicrobial agents into biofilms. However, the mechanisms which influence the interactions between NPs and the biofilm matrix are not yet fully understood.Methods: To investigate the influence of NPs surface chemistry on vancomycin (VAN) encapsulation and NP entrapment in MRSA and MSSA biofilms, mesoporous silica nanoparticles (MSNs) with different surface functionalization (bare-B, amine-D, carboxyl-C, aromatic-A) were synthesised using an adapted Stöber method. The antibacterial efficacy of VAN-loaded MSNs was assessed against MRSA and MSSA biofilms.Results: The two negatively charged MSNs (MSN-B and MSN-C) showed a higher VAN loading in comparison to the positively charged MSNs (MSN-D and MSN-A). Cellular binding with MSN suspensions (0.25 mg mL− 1) correlated with the reduced viability of both MSSA and MRSA biofilm cells. This allowed the administration of low MSNs concentrations while maintaining a high local concentration of the antibiotic surrounding the bacterial cells.Conclusion: Our data suggest that by tailoring the surface functionalization of MSNs, enhanced bacterial cell targeting can be achieved, leading to a novel treatment strategy for biofilm infections.Keywords: Staphylococcus aureus, mesoporous silica nanoparticles, EPS matrix, antimicrobial, vancomycin, nanoparticle-biofilm interactions